Finding the extreme efficient solutions of multi-objective pseudo-convex programming problem - Alireza Fakharzadeh Jahromi; Hassan Rostamzadeh (AUT Journal of Mathematics and Computing)
In this paper, we present two methods to find the strictly efficient and weakly efficient points of multi-objective programming (MOP) problems in which their objective functions are pseudo-convex and their feasible sets are polyhedrons. The obtained efficient solutions in these methods are the extreme points. Since the pseudo-convex  functions are quasi-convex as well, therefore the presented methods can be used to find efficient solutions of the (MOP) problem with the quasi-convex objective functions and the polyhedron feasible set. Two experimental examples are presented.